STUDENT TEACHERS’ MOTIVES IN ENTERING ENGLISH EDUCATION PROGRAM OF BATANGHARI UNIVERSITY - Kartika Dewi; Mohd Habibi (Universitas Singaperbangsa Karawang, 2017)
The purpose of this research is to describe the Student Teachers’ Motives in Entering English Education Program of Batanghari University. This research was conducted as qualitative research by using questionnaire and interview. The participants of this research are five males and five females of English Education Program who had passed the 4th semester and whose GPA were more than 3,00. In questionnaire there are 14 questions. The result of this research shows that Student Teachers’ Motives in Entering English Education Program are coming from the extrinsic motive in which almost all students think about their goal after finishing the study in the university such as finding job as an English teacher, working in a company, and international hotel to get much money for the better future. Keywords: student teachers’, motives.